DSM-IV and DSM-5 social anxiety disorder in the Australian community. (March 2015) - Crome, Erica; Grove, Rachel; Baillie, Andrew J; Sunderland, Matthew; Teesson, Maree; Slade, Tim
Objective: Current and accurate estimates of prevalence, correlates, comorbid concerns and treatment-seeking behaviours associated with disorders are essential for informing policy, clinical practice and research. The most recent snapshot of social anxiety disorder in Australia was published more than a decade ago, with significant changes to the accessibility of mental health treatment services and diagnostic measures occurring during this period. This paper aims to (i) update the understanding of social anxiety disorder, its associations and patterns of treatment-seeking behaviours in the Australian population, and (ii) explore the impact of revised diagnostic criteria detailed in the Fifth Edition of the Diagnostic and Statistical Manual of Mental Disorders (DSM-5) on prevalence estimates. Methods: The National Survey of Mental Health and Wellbeing (NSMHWB) was conducted by the Australian Bureau of Statistics in 2007, collecting information from a nationally representative random sample of 8841 Australians aged 16–85 years. The presence of social anxiety disorder diagnostic criteria and related disorders were assessed over 12 months and lifetime periods using the World Mental Health Composite International Diagnostic Interview. Results: Profiles of social anxiety disorder were consistent with previous estimates, with higher prevalence in females and younger age groups. Of the 8.4% of Australians meeting criteria for social anxiety disorder at some point in their lifetime (12-month prevalence 4.2%), a majority also experienced comorbid mental health concerns (70%). The revised performance-only specifier included in the DSM-5 was applicable to only 0.3% of lifetime cases. Just over 20% of people reporting social anxiety disorder as their primary concern sought treatment, most commonly through general practitioners. Conclusions: Social anxiety disorder continues to be prevalent in the Australian population and highly related to other disorders, yet few people experiencing social anxiety disorder seek treatment